Appreciation of the Ethnobotany of Carica (Vasconcellea pubescens A.DC.) by the Dieng Plateau Local Community - Adelisa, Septi Nur; Indah, Novita Kartika; Ningrum, Linda Wige (Jurnal Riset Biologi dan Aplikasinya, 2024)
Carica (Vasconcellea pubescens A.DC.) is a mountain papaya species with limited distribution in Indonesia, found in the Dieng Plateau, Central Java. Carica is well utilized by the Dieng Plateau community based on its local knowledge system. The decline of local knowledge is increasingly worrying, necessitating documentation efforts through ethnobotanical studies. This study aimed to examine the appreciation of the local community of the Dieng Plateau towards Carica ethnobotany. This study was descriptive research employing both qualitative and quantitative approaches, with interview techniques. The study was conducted in three Dieng Plateau villages: Dieng, Sembungan, and Karangtengah villages. The 30 respondents were selected by purposive and snowball sampling. The research instruments included interview guides and questionnaires. Appreciation was analyzed descriptively with a quantitative approach using a Likert scale. The results showed an excellent appreciation for preserving Carica in the surrounding environment (97.3%), while there was a low appreciation for using Carica to treat certain diseases (38%). Based on age, the elderly category showed the best appreciation for Carica utilization. Appreciation as a practice of local knowledge in the management and utilization of Carica can contribute to the conservation of Carica in the Dieng Plateau.